Implementasi Sipeta Untuk Identifikasi Pohon Berbasis QR Code di Kawasan Wisata Religi - Tey Seran, Krisantus Jumarto; Blegur, Willem Amu (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2023)
This article written based on the Community Service activity that was carried out according to the issue of utilization of the QR-Code based Sipeta application for tree growthform identification on religious area. The visitors do not have information about the name, taxonomy, use and status of trees in the location. Previous research using a QR-Code-based information technology approach has resulted in the SIPETA application. The SIPETA application (Plant Logging Information System) was developed to carry out digital mapping or identification of trees in our ecosystem, especially on dry land. This application was developed to simplify the technique of selecting species or tree species. The tree species database has been stored in the system. When a user or users use this application, it is enough to scan the QR-Code that is available on various types of trees. There are several stages and work plans that will be carried out by the Service Team in completing the objectives of this PkM activity, including: a) holding discussions with the manager of the Maria Siti Bitauni Cave area, b) identifying and making a QR-Code, c) installing a QR-Code on trees in this forest area, d) training on reading the QR-Code of trees using a smartphone, monitoring and evaluating the impact of SIPETA implementation. The application of the QR Code-based SIPETA application has helped the community and visitors to recognize and obtain information that is faster, easier and quite accurate for tree planting in the Maria Siti Bitauni cave area.